Effect of Sugar on Anthocyanins in Rosella Kombucha Drink - Catur Retno Lestari; Umar Hidayat; Lusiana Cici Sabarani (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2024)
Rosella kombucha is a fermented drink with a high antioxidant content and is known to be a solution that can neutralize free radicals and prevent oxidative stress. The ingredients in rosella kombucha drinks are anthocyanins, flavonoids, vitamin C, and polyphenols. Anthocyanin is a natural color pigment produced by plants. Anthocyanin is an antioxidant that is beneficial for the body. The fermentation process for the rosella kombucha drink was carried out for 14 days. This research aimed to determine the effect of sugar concentration on anthocyanin levels in rosella (Hibiscus sabdariffa L.) kombucha drinks. The method used in this research is quantitative experimental with a completely randomized research design (RAL) with 3 samples and 3 repetitions. The independent variable in this study is sugar concentration, while the dependent variable is anthocyanin content. The subject of this research is sugar concentration, with concentrations of 15%, 25%, and 35%. Anthocyanin levels were measured using a visible spectrophotometer using a wavelength of 700 nm. Data analysis used in this research used the Shapiro-Wilk test and the One Way ANOVA test. The results of the data analysis show that the highest average is found in the F3 sample at 38.743900 ppm. The results of data analysis using the One Way ANOVA test showed a p-value <0.05, which means it has a real influence. The lowest pH value was found in sample F3, namely 2. The low pH helped stabilize the anthocyanin levels in the Rosella kombucha drink. The results showed that the sugar concentration used to make rosella kombucha drinks in all samples had a significant influence on anthocyanin levels (p<0.05).